The impact of economic policy uncertainty on innovation types in enterprises: an empirical study of Chinese listed companies - Tang, Guoru; Zaghlol, Azlul Kalilah; Keshminder, J.S. (Universiti Teknologi MARA Selangor, 2025)
This study investigates the heterogeneous effects of economic policy uncertainty (EPU) on different types of enterprise innovation, namely invention patents, utility model patents, and design patents, based on a panel dataset of A-share listed companies in China from 2007 to 2022. Employing a random-effects Tobit model to address the left-censoring nature of patent data, the analysis reveals that EPU significantly suppresses innovation across all categories, with the strongest inhibitory effect observed on invention patents. The influence of EPU is further moderated by firm-level characteristics such as market power and profitability, as well as regional institutional environments. Monopolistic firms reduce radical innovation under uncertainty, while higher profitability, and research and development (R&D) intensity consistently promote innovation output. Regional comparisons show that eastern firms emphasise short-cycle innovations, western firms benefit from policy subsidies supporting core technologies, and central firms lag across all innovation dimensions. Robustness checks using alternative EPU indices and instrumental variable techniques confirm the reliability of the findings. The study concludes with tailored policy recommendations aimed at stabilising the innovation climate and enhancing inter-regional coordination.